OPSERVACIJA RVAČKOG SPORTA SA ZDRAVSTVENO-VASPITNOG ASPEKTA - Zoran Obradović; Goran Kasum (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
In the topic, wrestling has been observed through medical and educational aspects. In that point of view, observation of the best wrestling characteristics has been made. Using these, we can make an influence on educational and health state within young people. With this approach the aim and tasks, which contain specific psycho-motoric space of wrestling, have been determined. This brings us to conclusion that, through determined, this specific psycho-motoric space represent start point for further analytic observation. These would recommend wrestling, to some new system of calocagatia.